1993
DOI: 10.1093/oxfordjournals.humrep.a137916
|View full text |Cite
|
Sign up to set email alerts
|

Andrology: Variability of human sperm response to immediate and prolonged exposure to pentoxifylline

Abstract: Pentoxifylline improves some motility characteristics of human spermatozoa, but the variability of response to this drug has not been clearly defined. We used computer-assisted sperm motion analysis to examine the in-vitro response of spermatozoa to pentoxifylline. Individuals (n = 31) with normal sperm counts were randomly selected and their spermatozoa exposed to different concentrations of pentoxifylline. Further tests on a subgroup of individuals examined the longevity of spermatozoa in response to this ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
2

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 0 publications
0
12
1
2
Order By: Relevance
“…These findings differ from previous studies using cryopreserved human spermatozoa (Wang et al, 1993) and washed fresh spermatozoa (Moohan et al, 1993), in that a lower concentration of pentoxifylline was found to be optimal. However, considerable inter-individual variability in response to pentoxifylline has been reported which has not been adequately explained (Moohan et al, 1993). In our study, substantial inter-individual variation in response to pentoxifylline-supplemented cryoprotectant was observed (unpublished data).…”
Section: Discussioncontrasting
confidence: 99%
“…These findings differ from previous studies using cryopreserved human spermatozoa (Wang et al, 1993) and washed fresh spermatozoa (Moohan et al, 1993), in that a lower concentration of pentoxifylline was found to be optimal. However, considerable inter-individual variability in response to pentoxifylline has been reported which has not been adequately explained (Moohan et al, 1993). In our study, substantial inter-individual variation in response to pentoxifylline-supplemented cryoprotectant was observed (unpublished data).…”
Section: Discussioncontrasting
confidence: 99%
“…Pentoxifilline and other phosphodiesterase inhibitors are well known to stimulate the motility of spermatozoa, especially when it is poor initially (Garbers et al, 1971; Aitken et al, 1983; Rees, et al, 1990). More recent studies with computerized motility analyses agree that the greatest effects are on curvilinear velocity (VCL) and lateral head displacement (ALH), leading some authors to conclude that pentoxlfylline increases the proportion of hyperactivated spermatozoa (Tesarik et al, 1992a;Kay et al, 1993;Lewis et al, 1993;Mbizvo et al, 1993;Moohan et al, 1993;Pang et al, 1993). However, in the present study, in the presence of A23187 which has a deleterious effect on sperm mothty (Ford et al, 1991;McLaughlin et al, 1993), both 0.6 and 3.6 mmol pentoxifylline per litre fkrther decreased the proportion of spermatozoa which were motile.…”
Section: Discussionmentioning
confidence: 99%
“…PTX has been considered to stimulate flagellar motility by increasing sperm intracellular cAMP (Stefanovich, 1973;Garbers & Kopf, 1980;Tash & Means, 1983;Ward & Clissold, 1987) as well as by reducing sperm intracellular superoxide anion and reactive oxygen species known to damage DNA (Lopes et al, 1998;Twigg et al, 1998). In particular PTX in both in vivo and in vitro studies, appears to increase significantly beat cross frequency, curvilinear velocity, and the percentage of hyperactivated spermatozoa (Rees et al, 1990;Shen et al, 1991;Lewis et al, 1993;Moohan et al, 1993;Pang et al, 1993;Tournaye et al, 1994;Centola et al, 1995;Paul et al, 1996;Nassar et al, 1999).…”
Section: The Development Of In Vivo Studiesmentioning
confidence: 99%